AOIR ETHICS IN ACTION: GUIDELINES, REGULATIONS, AND PRACTICES ACROSS DIVERSE GLOBAL COMMUNITIES - Zimmer, Michael; Vitak, Jessica; Lenhart, Anna; Hård af Segerstad, Ylva; Hartvigsson, Thomas; Bergviken-Rensfeldt, Annika; Hillman, Thomas; Brown, Megan; Gruen, Andrew; Maldoff, Gabe; et al. (AoIR Selected Papers of Internet Research, 2026)
Since its inception, the Association of Internet Researchers (AoIR) has fostered critical reflection on the ethical and social dimensions of the internet and Internet-facilitated communication and interactions. The AoIR Ethics Working Committee has been committed to ensuring the AoIR Ethics Guidelines remain helpful and relevant to researchers and ethical review committees; our goal is to support ethical decision-making in internet research by keeping the guidelines responsive to emerging technologies, evolving research practices, and the diverse needs of scholarly and practitioner communities. This panel includes five papers that engage in “AoIR Ethics in Action” – demonstrating how the AoIR Ethics Guidelines and their core principles are applied, interpreted, and shaped across diverse, global contexts. The presentations explore internet researchers’ preparedness and design-making processes related to the ethics of their work; how the emerging regulatory frameworks in the U.S. and Sweden illuminate evolving challenges in research ethics; and examine how the guidelines can inform ethical decision-making in specific cases, such as web scraping and the use of Wikipedia data. RESEARCH ETHICS PRACTICES & PREPAREDNESS: A STUDY OF AOIR & ICA This paper reports on survey results from internet researchers in AoIR and ICA to assess their engagement with ethical guidelines and preparedness for handling ethical dilemmas in digital data collection. The findings indicate potential gaps in ethical preparedness and training, emphasizing the need for updated AoIR Ethics Guidelines and stronger institutional support for researchers dealing with pervasive data ETHICAL CHALLENGES IN PERVASIVE DATA RESEARCH: STAKEHOLDER PERSPECTIVES AND PATHS FORWARD This report analyzes responses to a U.S. NTIA Request for Comment on ethical guidelines for pervasive data research, identifying core tensions such as legal/definitional ambiguities, anonymization limitations, and the challenge of balancing ethical principles when performing research with large-scale datasets. It argues that researchers and civil society must proactively strengthen ethical research practices in the absence of clear government guidelines. ETHICS IN TRANSITION: ADAPTING RESEARCH GOVERNANCE TO A PROPOSED NEW NEW LEGAL FRAMEWORK IN SWEDEN This contribution examines Sweden’s shift toward decentralized research ethics governance under a proposed legal reform, which will transfer responsibility for ethical review from national boards to individual institutions. It explores tensions between standardized regulations and local adaptations, highlighting potential risks such as institutional disparities and legal uncertainties for interdisciplinary digital research. WHEN IS SCRAPING LEGITIMATE? ETHICAL, LEGAL, ADMINISTRATIVE, AND TECHNICAL CONSIDERATIONS This white paper presents a comprehensive framework for web scraping in social science research, examining the legal, ethical, institutional, and scientific factors that researchers must consider when scraping the web. It presents an overview of the current regulatory environment impacting when and how researchers can access, collect, store, and share data via scraping, offering researchers guidance on best practices to balance data access with responsible research ethics. RESEARCH AND PRIVACY ON WIKIPEDIA This white paper examines the ethical and privacy challenges of conducting research on Wikipedia, emphasizing concerns about re-identification, user anonymity, and community expectations. It proposes best practices for researchers and Wikipedia users to help navigate ethical tensions while ensuring transparency, user safety, and adherence to privacy norms. Together, these papers illustrate the ongoing relevance of the AoIR Ethics Guidelines in navigating the complex ethical, legal, and regulatory landscape of internet research.